Lyme disease of the CNS: MR imaging findings in 14 cases. - Fernandez, R E; Rothberg, M; Ferencz, G; Wujack, D (American Journal of Neuroradiology, 1990)
The MR images of 14 patients with clinical diagnoses of Lyme disease, CNS complaints, and positive Lyme titers were reviewed. MR examinations were abnormal in 43%. Areas of abnormal signal were identified within the cerebral white matter as well as within the brainstem.